Material Culture, the Public, and the Extraordinary – “Unloved” Museums Objects as the Tool to Fascinate - Zinn Katharina (Open Archaeology)
Museum-excavations – discovering unprovenanced and forgotten objects in museums’ storerooms – open new opportunities for engagement and highlight the consequent necessity to (de-)contextualise the discovered artefacts. Despite being unprovenanced – or even because of that – it is important to make sense of these “ordinary” finds. Developing strategies of unmasking the EXTRAordinary within such objects – an approach which I presented in my work Narrating the Extra the Ordinary has: “Re-excavating” objects in storage rooms of local museums as part of an archaeology of unloved objects as part of the workshop “Excavating the Extra-Ordinary - Challenges & merits of working with small finds” (JGU Mainz, 08–09 April 2019 – Zinn, 2019b) – and communicating them as part of imaginative activities for the wider public and the research community has been at the core of the described cooperative project, aiming at the literal and cultural (re-)discovery of ancient Egyptian artefacts. As Cyfarthfa Castle Museum and Art Gallery serves the local South Wales valleys, it was seen difficult to incorporate the Egyptian collection into the narrative of the museum’s permanent exhibition. The project brings these objects back to life by simultaneously creating different types of cultural representations via academic outputs, exhibitions, storytelling, a Museum of Lies, and artwork inspired by the items. All these methods centre on the materiality of the objects from which different meanings are drawn. This approach connects these objects with several identities in which they are placed. The engagement with all audiences/stakeholders proved crucial for the success of this project and leads to a sustainable interaction with neglected artefacts.